Evaluation of the plaque removal efficacy of xylitol-impregnated single-use toothbrush in vivo in 10-11-year-old children - Tezer Ulusu; Gizem İnan; Ali Affan Kurt (Gazi University, 2017)
Objective: Xylitol is non-fermentable by oral bacteria and it inhibits the growth, metabolism and polysaccharide production of mutans streptococci, resulting in less bacterial plaque accumulation on teeth. This study aimed to compare the plaque removal efficacy on the teeth of children of xylitol-impregnated or non-impregnated single-use toothbrushes identical in shape and manufactured by the same company. Materials and Method: Thirty children aged 10-11 years were randomly separated into two groups of 15 children each. First group used a xylitol-impregnated toothbrush and the second group used a non-impregnated toothbrush for brushing. Dental plaque on upper central incisors was photographed intra-orally before and after brushing under standardized conditions. These photographs were stored in a computer and the amount of dental plaque was scored by using Turensky Modified Quinley Hein Plaque Index by a researcher blinded to the groups. Results: While both xylitol-impregnated and non-impregnated groups had significantly higher plaque index in before-brushing photographs than after-brushing photographs (p<0.05), no significant difference existed between the two groups (p>0.05). Conclusion: The results of the study emphasized that toothbrushing itself, regardless of xylitol content within the toothbrush, is essential for removing the dental plaque.